TOWARDS URBAN FARMING: INTERNET OF THINGS INDOOR BASED RICE PLANTING WITH SMS ALERT NOTIFICATIONS - Aranda, Jonalyn Mae E; Bersabe, Julius Arvin V; Cahiyang, Jerome L; Cruzat, Vanessa Jane M; Dedil, Rho Jean Mark C; Pijana, Deejhay S (Journal of Agriculture and Technology Management; Vol 24 No 3 (2021): Vol 24 No 3 (2021): Vol 24 No 3 (2021): Journal of Agriculture and Technology Management (JATM) Volume 24 ICAMEROB Edition, 2021)
The purpose of this study is to “achieve an environment indoors where the researchers can cultivate rice and tilapia in one system – aquaponics system.” Aquaponics is a combination between aquaculture (farming of fish) and hydroponics (growing plants without soil), being a technique to grow plants with aquaculture effluent. Tilapia fish will provide nutrients for the rice plants, and the rice will consume the fish excreted waste. The study consists the Internet of Things (IoT) Aquaponics system consists of five (5) sensing device – pH sensor, room temperature and humidity sensors, water temperature sensor, water flow sensor, and non-contact liquid sensor. The sensor readings would be sent to the Thing Speak acquiring of real time data which is the database of the system for information utilization. If the acquired data is not within the threshold range, a SMS (Short Message Service) operated by Twilio will be sent to the end user for alert notification. The Twilio is an Android Package Kit (APK) for the android phone. It was created using Massachusetts Institute of Technology (MIT) App Inventor to display the stored sensor readings in the database and to be able to give suggestions to the user as it monitor the parameters of the system.